Symptomatic right ventricular ischemia secondary to a critical stenosis in a nondominant right coronary artery1. Issue 1 (15th March 2012) - Flynn, Shawn E.; Sachdeva, Rajesh; Uretsky, Barry F.
Abstract Stable angina pectoris owing to isolated right ventricular ischemia from a critical stenosis in a nondominant right coronary artery is a rare entity and documentation of isolated right ventricular ischemia even rarer. We present a case of isolated right ventricular ischemia documented by fractional flow reserve (FFR) and resolution of symptoms after percutaneous coronary intervention. © 2012 Wiley Periodicals, Inc.